Incorporating intra-lesional injection of mitomycin C in the management algorithm for bladder neck contractures and vesicourethral anastomotic strictures. (January 2022) - Yao, Henry H; Sengupta, Shomik; Chee, Justin
Objective: This study aims to describe the experience of a single-surgeon series with the use of intra-lesional mitomycin C (MMC) in the treatment of bladder neck contracture (BNC) and vesicourethral anastomotic stenosis (VUAS). Patients and methods: From July 2014 to January 2019, patients who underwent bladder neck incision (BNI) and intra-lesional MMC injection performed by a single surgeon were included in this retrospective study. Clinico-pathological data were extracted from medical records. The primary outcome was recurrence rate following BNI and MMC injection. Results: Ten patients were included in the study. The median age was 68 years. The cause of BNC or VUAS was secondary to radical prostatectomy in eight patients and to endoscopic prostatectomy in two patients. The median follow-up was 16.4 months. The success rate was 70% after first treatment with BNI and MMC injection, and 80% after repeated treatment. There were no serious adverse events or complications related to the MMC injection. Conclusion: BNI and intra-lesional MMC injection is a minimally invasive treatment for refractory bladder neck contractures with a good success rate and minimal risk of side effects when a low dose of MMC is used. Further prospective multicentre study is warranted. Level of evidence: Level 4.